Hubungan Ibu-Anak Perempuan dengan Regulasi Emosi Mahasiswi Fakultas S1 Ilmu Keperawatan - Dewi Maulidah; Riza Arisanty Latifah; Maulida Nurapipah (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
A student has their own way of solving a problem faced when they are in a stressful situation. One of the things that determines individual emotion regulation strategies is the social support provided by the family, the role of a mother being a common result that represents the relationship between parents and children in the family. The aim is to determine the relationship of various dimensions of mother-daughter relationship with emotion regulation of 2019 batch of female students, Faculty of S1 Nursing Science, Universitas Muhammadiyah Cirebon. This type of research is quantitative research with a cross sectional design. The study population was 90 respondents. The sampling technique was total sampling. Statistical tests using Chi Square. The research tool was a questionnaire. The results of the analysis based on the Chi Square test show that the ? value of the connectedness subscale in the mother-daughter relationship has no relationship with the level of emotional regulation, with a sig value of 0.307 (p-value 0.05). The interdependency subscale in the mother-daughter relationship has no relationship with the level of emotion regulation, with a sig value of 0.451 (p-value 0.05). The trust in hierarchy subscale in the mother-daughter relationship has no relationship with the level of emotion regulation, with a sig value of 0.076 (p-value 0.05). Parents need to continue to improve communication skills with children, by teaching self-control including emotional management in a child.